STANDARDIZATION OF EFFORT PARAMETERS IN ACCORDANCE WITH THE PHYSIOLOGICAL CHARACTERISTICS OF WOMEN APPLIED IN HANDBALL. A SYSTEMATIC REVIEW - POPESCU, Octavian; PETRACOVSCHI, Simona (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Introduction: Female handball is an intermittent sport with heavy physical contacts that requires alternating high-intensity actions over short periods of time with low-intensity actions. Resistance training improves muscular endurance, muscular strength, power, velocity and agility. Performing sport-specific motor skills with high values of these qualities in handball influences the final result. During a general resistance exercise performed at moderate to high intensity, women oxidize more fat and less carbohydrates compared with men at the same relative intensity. For this reason, women will have a lower level of muscle fatigue. Purpose: Standardization of volume and intensity to the female particularities and handball specific motor skills. Research methods: The PRISMA diagram was used to determine the studies that met the inclusion criteria for systematic analysis. A total of 363 female who play handball were included. Results: Women can perform more repetitions compared with men at an intensity between 40–60% of maximal strength. The best values for resistance training are reached by performing a number of 20–28 RM. Conclusion: A discrepancy was found between the physiological particularities of the female sex and the standardization of effort parameters in the training plans of the studies included in this analysis.